PENGEMBANGAN MODEL TGT BERBANTUAN SNAKES LADDERS BERBASIS GENIALLY WEB MATERI PANCASILA SEBAGAI NILAI KEHIDUPAN (SISWA KELAS IV SD NEGERI GAPRANG 01 KABUPATEN BLITAR) - Ajeng Ayu ANggita; Shofi Nur Amalia; Khoirul Wafa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
TGT model assisted by Genially Web-based Snakes Ladders. At SD Negeri Gaprang 01 Blitar Regency, grade IV students face difficulties in understanding Pancasila Education lessons even though the material has been neatly arranged by the teacher but students do not like Pancasila Education lessons causing problems in the learning process, namely: students have difficulty focusing on learning, many students tend to play alone in the midst of learning activities, there is no factor of variation in teaching models and learning media that leads to a monotonous learning experience. To overcome this problem, researchers developed a TGT model assisted by Genially Web-based Snakes Ladders. The TGT model is cooperative learning that forms students learning in small groups of 5-6 people. This model adds an element of fun, makes the learning experience creative, entertaining and increases students' interest in learning. Genially is a web-based platform that is used to assist users in creating various audiovisual and interactive content and can attract students' interest in learning. The purpose of the researcher developing the TGT model assisted by Genially Web-based Snakes Ladders is to determine the validity and attractiveness of the TGT model assisted by Genially Web-based Snakes Ladders media. The strategy used in this research is Research and Development (R&D) with the PPE model which consists of three stages:  Planning, Production, Evaluation. The results of learning design validation obtained 90% and 95% material experts as well as the percentage of teacher attractiveness of 93% and the results of student attractiveness obtained 97%. The TGT model assisted by Genially Web-based Snakes Ladders is expected to attract students' interest in learning and can help the learning process.